Helicopter parenting during emerging adulthood: Consequences for career identity and adaptability - LeBlanc, Joshua E.; Lyons, Sean T. (Frontiers in Psychology, 2022)
Abstract: This study explores the relationship between parental over involvement and the career development of emerging adults. Specifically, it investigates how emerging adults’ career meta competencies of vocational identity formation and career adaptability relate to perceived helicopter parenting. Participants included 491 emerging adults studying in a Canadian University (74.1% female, average age = 20.4 years old). We begin by reviewing the commonalities between helicopter parenting and other parenting constructs and styles. Next, using structural equation modeling, we explore the relationships between perceived helicopter parenting and the components of vocational identity (exploration: in depth exploration, in breadth; commitment: career commitment, identification with commitment; and reconsideration: career self doubt, career flexibility) and career adaptability, as well as the relationships between identity components and career adaptability. Third, we explore the association between perceived helicopter parenting and identity status progress (i.e., achievement, foreclosure, moratorium, undifferentiated, and searching moratorium). Results indicate that individuals reporting higher levels of perceived helicopter parenting experience significantly lower levels of career adaptability and in-depth exploration. Furthermore, these individuals report higher levels of career self doubt and are more likely to be in the vocational identity status of searching moratorium. Limitations and future research directions are discussed.